A Single-Inductor Bipolar-Output DC-DC Converter With Tunable Asymmetric Power Distribution Control (APDC) for AMOLED Applications - Wei-Ting Yeh; Meng-Xun Cai; Chien-Wu Tsai; Chien-Hung Tsai (IEEE Access)
This paper presents a single-inductor bipolar output (SIBO) converter with tunable asymmetric power distribution control (APDC) for active-matrix organic light-emitting diode (AMOLED) display applications. This power stage architecture requires only a single external inductor to provide the bipolar voltages needed for the AMOLED pixel circuit. In AMOLED applications, the specifications for positive voltage are more stringent than for negative voltage. This work implements the APDC technique to deliberately sacrifice the transient performance of the negative voltage within acceptable limits to depress the over/undershoot voltage magnitude of the positive voltage. For design completion, a skipping mode is introduced to improve power conversion efficiency by 14% to 17%. The proposed SIBO DC-DC converter, fabricated using TSMC’s 0.18um 1.8V/3.3V 1P6M Mixed Signal process, is suitable for load ranges from 20mA to 200mA. With the APDC technique, the positive transient overshoot voltage is improved from 4.66% to 0.82%, and the undershoot voltage from 5.32% to 1.08%. The results validate the effectiveness of the proposed APDC technique.